THE EFFECT OF GAMBLING ON THE OCCURRENCE OF PROPERTY CRIME - Gunawan Widjaja; Wagiman Martedjo; Yohanes Khristoforus (INJOSEDU: International Journal of Social and Education, 2025)
Gambling has long been a social problem that can have a significant impact on the lives of individuals, families and society as a whole. This study aims to analyse the effect of gambling on the incidence of property crime, both in terms of income and losses caused by gambling habits in society. The data used in this study were obtained from the North Jakarta Police. Gambling, which is an activity involving betting money or goods with results dependent on luck, is often associated with various forms of crime. Property crimes such as theft, robbery, and fraud can be triggered by an individual's dependence on uncontrolled gambling. In this research, it is carried out normatively where gambling is an act prohibited by law and anyone, be it a new gambler or a recidivist who commits gambling, is subject to criminal law sanctions. As a result of the influence of gambling, it creates criminal motives (such as theft, fraud, and embezzlement), weakens self-control to commit crimes, and causes losses to other people's property. Normatively, gambling is regulated by laws in Indonesia such as the Criminal Code (KUHP) Article 303, Regional Regulations (Perda). The results showed that although gambling can provide short-term benefits, in the long run, gambling addiction often causes losses.